Hippasteria falklandica Fisher 1940 - Mah, Christopher; Nizinski, Martha; Lundsten, Lonny (Zenodo, 2010)
HIPPASTERIA FALKLANDICA FISHER, 1940 Fisher, 1940: 125; Bernasconi, 1973: 287; Clark & Downey, 1992: 247; Stampanato & Jangoux, 2004: 6; McKnight, 2006: 97 Occurrence: Falkland Islands (=Islas Malvinas), northern Argentina, Marion and Prince Edward Islands region to south of Tasmania, approx. 49°S, 150°E. 225–1148 m. Material examined: None. : Published as part of Mah, Christopher, Nizinski, Martha & Lundsten, Lonny, 2010, Phylogenetic revision of the Hippasterinae (Goniasteridae; Asteroidea): systematics of deep sea corallivores, including one new genus and three new species, pp. 266-301 in Zoological Journal of the Linnean Society 160 (2) on page 286, DOI: 10.1111/j.1096-3642.2010.00638.x : {"references": ["Fisher WK. 1940. Asteroidea. Discovery Reports 20: 69 - 306.", "Bernasconi I. 1973. Los equinodermos colectados por el Walther Herwig en el Atlantico Sudoeste. Revista del Museo Argentino de Ciencias Naturales 3: 287 - 334.", "Clark AM, Downey ME. 1992. Starfishes of the Atlantic. London: Chapman and Hall.", "Stampanato S, Jangoux M. 2004. The asteroid fauna (Echinodermata) of Marion and Prince Edward Islands. Annals of the South African Museum 112: 1 - 16.", "McKnight DG. 2006. The Marine Fauna of New Zealand: Echinodermata: Asteroidea (sea stars). 3. Orders Velatida, Spinulosida, Forcipulatida, Brisingida with addenda to Paxillosida, Valvatida. NIWA Biodiversity Memoir 120: 1 - 187."]}